Exploring the relationship of transport network and land use patterns: an approach through weighted centrality assessment - Jagannath Das; Sewa Ram (Urban, Planning and Transport Research)
This study investigates the relationship between transport networks and land use patterns in the Delhi Metropolitan Area by employing a weighted centrality assessment approach. Recognizing the limitations of traditional monocentric and accessibility-based urban models, this study introduces a multimodal perspective that integrates both road and rail systems. Land use patterns are scrutinized in terms of spatial distribution of Residential, commercial, Public semipublic (PSP)/institutional, industrial and other landuse. Weighted centrality measures are assessed in terms of closeness, betweenness, and straightness, applied within a weighted framework to reflect the multimodal transport characteristics. This study introduces a path evaluation function (PEF) that incorporates transport network capacity and travel time and is calibrated with a turning parameter (α). Through multinomial logistic regression, we explore the complex relationship between weighted centrality of transport network and land use patterns. Results reveal a significant relationship, underscoring that higher centrality tends to favor commercial and public-semi-public/institutional uses, whereas centrality at lower spectrum favors the development of residential areas. This research not only advances the theoretical understanding of urban planning but also offers practical insights for policymakers, emphasizing the importance of multimodal transport considerations in urban development.